Pregnancy Outcomes Associated With a Single Elevated Blood Pressure Before 20 Weeks of Gestation. Issue 1 (July 2021) - Duffy, Jennifer Y.; Getahun, Darios; Chen, Qiaoling; Fong, Alex
Abstract : OBJECTIVE: To evaluate maternal and fetal outcomes among women with a single elevated blood pressure before 20 weeks of gestation. METHODS: We conducted a retrospective cohort study of women who delivered at Kaiser Permanente Southern California hospitals between January 1, 2008, and December 31, 2019. Participants were divided into two groups: normotensive (all systolic blood pressures lower than 130 mm Hg and diastolic pressures lower than 80 mm Hg) compared with single elevated blood pressure (single systolic pressure 130 mm Hg or higher, diastolic pressure 80 mm Hg or higher, or both). Women with chronic hypertension were excluded. Maternal comorbidities and maternal and neonatal outcomes were extracted from electronic health records using International Classification of Diseases codes. Adjusted odds ratios (aORs) derived from logistic regression were used to describe the magnitude of association. RESULTS: Of 303, 689 women who delivered during the study period, 23% had a single elevated blood pressure. Rates of hypertensive disorders of pregnancy differed between the two groups (10.6% for single elevated blood pressure, 4.5% for normotensive group; aOR 2.06, 95% CI 2.00–2.13), as did iatrogenic preterm delivery (3.7% vs 2.7%, respectively; aOR 1.27, 95% CI 1.21–1.33). DISCUSSION: Women with a single elevated blood pressure before 20 weeks of gestation are at increased risk for hypertensive disorders of pregnancy and iatrogenic preterm delivery. Abstract : A single systolic blood pressure of at least 130 mm Hg, a single diastolic blood pressure of at least 80 mm Hg, or both, before 20 weeks of gestation is associated with the development of a hypertensive disorder of pregnancy.